Detection, identification, characterization, and high‐performance liquid chromatography quantification of five impurities from a methazolamide product. Issue 16 (24th July 2022) - Shen, Qirong; He, Quan; Pan, Yuanjiang; Sun, Cuirong
Abstract : Methazolamide is an important carbonic anhydrase inhibitor and is mainly used for the treatment of glaucoma. Studies are extremely rare regarding the impurities in methazolamide products. In this work, the high‐performance liquid chromatography/high‐performance liquid chromatography‐mass spectrometry methods were established for the analysis of impurities in methazolamide products. Five impurities (A, B, C, D, and E) were detected using the established high‐performance liquid chromatography/high‐performance liquid chromatography‐mass spectrometry methods. Of these impurities, impurities A, B, and D are known compounds, and impurities C and E are novel compounds that have never been reported before. The identities of impurities A, B, D, and E were recognized by comparing their retention times and mass spectra with those of synthesized standard compounds under the same high‐performance liquid chromatography‐mass spectrometry conditions. Moreover, the structures of impurities C and E were characterized using a variety of analytical techniques including multidimensional nuclear magnetic resonance spectroscopy, Fourier transforming infrared spectroscopy, ultraviolet‐visible absorption spectroscopy, and high‐resolution quadrupole time‐of‐flight mass spectrometry. All of the five impurities are structural analogs of methazolamide. The formation mechanisms of these impurities were discussed.